A new approach for estimating ocean‐surface wind speed using an SMAP L‐band radiometer. (24th December 2018) - Sharma, Neerja
Abstract : The measurement of ocean surface wind speed (WS) during cyclones plays a key role in improving cyclone track and intensity predictions; however, limited in situ WS observations during cyclone events are not sufficient for the continuous monitoring of intensity and track. Although satellite measurements provide an alternative means of obtaining such data, the performance of high‐frequency microwave (≥ 5GHz) sensors – which are used for ocean surface WS estimation – is adversely affected by rainy and high WS conditions. As a result, these frequencies cannot be used to measure WS under cyclonic conditions. However, since the L‐band (1.4GHz) microwave frequency is negligibly affected by atmospheric parameters such as water vapour, cloud and rain, it can be used to estimate ocean surface WSs even during cyclonic conditions. An L‐band microwave radiometer is currently in operation onboard the Soil Moisture Active Passive (SMAP) satellite, offering an opportunity to measure high WSs during cyclones. Although WS data from SMAP are available from Remote Sensing Systems (at http://www.remss.com/missions/smap/ ), a new retrieval technique using SMAP top‐of‐atmosphere horizontal and vertical polarised brightness temperature measurements (TOA_Tb) is presented here. Excess brightness due to the high WS of cyclones is clearly evident in the SMAP TOA_Tbs data. The technique described in this article produced estimates which successfully captured high wind speeds of up to ~50ms −1 during cyclones, and the WS values reported here are close to those from the Automated Tropical Cyclone Forecast. Abstract : The L‐band (1.4GHz) is the microwave frequency which is least affected by cyclonic conditions. The performance of space‐borne sensors that operate at higher frequencies (≥5GHz) declines under rainy and high wind speed conditions. A new retrieval technique is developed here which enables wind speed to be estimated during cyclones using an L‐band radiometer onboard the Soil Moisture Active Passive satellite. Brightness temperatures at the top of the atmosphere are used to estimate WS values (of up to ~50ms −1 ) during cyclonic conditions, under which measurement would not be possible using other microwave sensors.